A preliminary exploration of concussion and strength performance in youth ice hockey players - Reed, N.; Taha, T.; Monette, G.; Keightley, M. (International Journal of Sports Medicine, 2016)
The objective of this study was to describe the effect of concussion on upper and lower body strength in children and youth athletes. The participant group was made up of 178 unique male and female ice hockey players (ages 8-14 years). Using a 3-year prospective longitudinal research design, baseline and post-concussion data on hand grip strength, jump tests, and leg maximal voluntary contraction were collected. Using a linear mixed-effects model, no significant differences were found when comparing the baseline strength performance of individuals who went on to experience a concussion and those who did not. When accounting for sex, multiple concussions, and ongoing changes in strength associated with age, weaker hand grip scores were found following concussion while participants were still symptomatic. Lower squat jump heights were achieved while participants were symptomatic as well as when they were no longer self-reporting symptoms associated with concussion. This study represents an initial step towards better understanding strength performance following concussion that may limit the on and off ice performance of youth ice hockey players, as well as predispose youth to subsequent injuries.